The PI3K Inhibitor XH30 Enhances Response to Temozolomide in Drug-Resistant Glioblastoma via the Noncanonical Hedgehog Signaling Pathway - Ji, Ming; Zhang, Zhihui; Lin, Songwen; Wang, Chunyang; Jin, Jing; Xue, Nina; Xu, Heng; Chen, Xiaoguang (Frontiers in Pharmacology, 2021)
Glioblastoma multiforme (GBM) is the primary malignant tumor among central nervous tumors. Temozolomide (TMZ) based adjuvant treatment has improved the overall survival, but the clinical outcome is still not satisfied. TMZ resistance is one of the main reasons. Here, we reported a new PI3K inhibitor XH30 and assessed its antitumor activity against TMZ-resistant GBM. XH30 inhibited the cell proliferation in TMZ-resistant GBM cells (such as U251/TMZ and T98G) and induced cell cycle arrest in G1 phase. In mice orthotopic model, XH30 repressed TMZ-resistant tumor growth. Combination of XH30 with TMZ can enhance TMZ cytotoxicity In vitro and In vivo. Mechanically, the synergistic effect of XH30 attributed to its repression on key transcriptional factor Gli1 via noncanonical hedgehog signal pathway. XH30 reversed sonic hedgehog (Shh)-triggered Gli1 activation and decreased Gli1 activated by IGF-1 via noncanonical hedgehog signal pathway. These results indicated that XH30 is a potential choice for TMZ-resistant GBM treatment.